Hungry for trade : how the poor pay for free trade - Madeley, John (London : Zed Books, 2000)
Explores some key questions regarding the year 2000 World Trade Organisation (WTO) Agreement on Agriculture. Will free trade in food help or hinder the abolition of hunger - or will it chiefly benefit transnational corporations? Will free trade help small farmers find new markets in the North?
Introduction1. Seattle 19992. Food Security: The Causes of Insecurity3. Trade Liberalization4. International Organisations and Policies Affecting Trade and Food Security5. Trade Liberalization and Food Security: The Evidence6. Corporate Managed Trade: Patents7. Corporate Managed Trade: Genetically Modified Foods8. Putting Food Security Into Trade: NGOs Speak 9. Conclusion: Food Security With Less Trade?Conclusion
Includes bibliographical references and index.
Keywords: Food supply -- Developing countries; International trade; Developing countries -- Commerce